Comparison of keratometry assessment between IOLMaster and Pentacam in dry eyes - Fei Yang; Jiayin Qin; Xijuan Wang; Mingwu Li (Photodiagnosis and Photodynamic Therapy)
Background: To compare the keratometry measurements between IOLMaster and Pentacam in dry eyes. Methods: A total of 122 eyes of 95 age-related cataract patients with dry eye disease were enrolled in this study. Keratometry measurements including flat and steep keratometry (K), mean keratometry, axis of the flat K, astigmatism of anterior corneal surface (A-ACS) were obtained using IOLMaster and Pentacam. A second series of examinations were performed 1 min after instillation of artificial tears. Values of keratometry measured by two devices were compared both before and after using artificial tears. Changes of the above parameters in each device were also analyzed. Results: The mean flat K of IOLMaster was significantly lower than Pentacam. A-ACS was significantly larger in IOLMaster than in Pentacam, with a mean discrepancy of 0.46 D and an upper limit of 95 % LoA of 1.48 D. The 95 % LoA for flat K axis also exceeded the clinically relevant margin. Keratometry and A-ACS measurements were significantly modified after instillation of artificial tears. None of the above parameters showed significant difference between two devices except for A-ACS, with the mean difference decreased to 0.17 D with 95 % LoA of -0.20 to 0.54 D. Intra device comparison showed that changes of A-ACS and flat K axis measured with IOLMaster were greater than those measured with Pentacam. Conclusion: Dry eye has significantly greater impact on keratometry measured with IOLMaster than with Pentacam. For cases with A-ACS between the two devices over 0.5 D, artificial tears are recommended before performing biometry.